Z-Copy Controlled-Gain Voltage Differencing Current Conveyor: Advanced Possibilities in Direct Electronic Control of First-Order Filter - Sotner, R.; Herencsar, N.; Jerabek, J.; Prokop, R.; Kartci, A.; Dostal, T.; Vrba, K. (Elektronika ir Elektrotechnika, 2014)
A modified version of voltage differencing current conveyor (VDCC) and its performance in detail is presented in this paper. Modified VDCC, so-called z-copy controlled gain voltage differencing current conveyor (ZC-CG-VDCC), offers interesting features from adjustability point of view. The active element allows independent electronic control of three adjustable parameters: intrinsic resistance of current input terminal, transconductance and current gain of the output stage which is not possible in case of conventional VDCC. The characteristics of proposed CMOS implementation designed using TSMC LO EPI 0.18 m technology process parameters are shown and discussed. Simple application in reconfigurable reconnection-less first-order voltage-mode multifunctional filter is shown and verified by SPICE simulations and experimentally. The filter tuning and change of the transfer function type is allowed by the controllable parameters of the ZC-CG-VDCC. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7272